Detection of central venous catheter‐related bloodstream infections in haematooncological patients. (29th June 2015) - Rabensteiner, Jasmin; Theiler, Georg; Duettmann, Wiebke; Zollner‐Schwetz, Ines; Hoenigl, Martin; Valentin, Thomas; Leitner, Eva; Luxner, Josefa; Grisold, Andrea; Valentin, Angelika; Neumeister, Peter; Krause, Robert
Abstract Background Catheter‐related bloodstream infections (CRBSIs) are currently detected in patients with clinically suspicion. The aim of our study was to evaluate whether CRBSIs could be anticipated and detected in a subclinical stage by peptide nucleic acid fluorescence in situ hybridization (PNA FISH) using universal hybridization probes or acridine orange leucocyte cytospin (AOLC) tests in haematooncological patients with central venous catheters (CVCs) in situ. Materials and methods Peptide nucleic acid fluorescence in situ hybridization and AOLC tests using blood samples from one CVC lumen/port chamber in haematooncological patients were continuously performed. These results were compared to those obtained from routinely performed CRBSI diagnostic tests. Results One hundred and eighty‐two patients with 342 catheter periods were investigated. Seventeen CRBSI cases were detected in 6466 CVC days by routine measures resulting in a CRBSI rate of 2·6/1000 catheter days. Two of 17 showed positive PNA FISH tests, and five positive AOLC test results before the diagnosis were established with routine measures. The screening revealed further seven patients with positive universal PNA FISH tests and 10 positive AOLC tests without symptoms indicative for infection and were therefore considered not to have CRBSI. Conclusions Sampling of only one CVC lumen/port chamber screening for CRBSI in haematooncological patients seems not to be a useful tool for anticipative diagnosis of CRBSI. Reasons for false‐negative results might include origin of CRBSIs from the other CVC lumina not sampled for screening, and false‐positive results might origin from catheter colonization without subsequent spread of micro‐organisms into the peripheral bloodstream.